2008
DOI: 10.1111/j.1743-6109.2008.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Orgasm Is Associated with Less Use of Immature Psychological Defense Mechanisms

Abstract: Introduction Freud implied a link between inability to have a vaginal orgasm and psychosexual immaturity. Since Kinsey, many sexologists have asserted that no such link exists. However, empirical testing of the issue has been lacking. Aim The objective was to determine the relationship between different sexual behavior triggers of female orgasm and use of immature psychological defense mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
112
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(142 citation statements)
references
References 44 publications
(64 reference statements)
24
112
2
Order By: Relevance
“…This result provides further support that it is specifically PVI without condoms that is associated with healthy psychological function. Neurotic defenses tend to be associated with indices of psychological impairment (although less consistently so than are immature defenses) [28,36,40], but uncorrelated [38] or even positively associated with more specific measures of interpersonal functioning [37]. Thus, neurotic defenses might inhibit the seeking and obtaining of PVI without condoms, but (unlike immature defenses) without increasing the seeking of sexual activity with less emotional interaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result provides further support that it is specifically PVI without condoms that is associated with healthy psychological function. Neurotic defenses tend to be associated with indices of psychological impairment (although less consistently so than are immature defenses) [28,36,40], but uncorrelated [38] or even positively associated with more specific measures of interpersonal functioning [37]. Thus, neurotic defenses might inhibit the seeking and obtaining of PVI without condoms, but (unlike immature defenses) without increasing the seeking of sexual activity with less emotional interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Validity studies using the DSQ‐40 demonstrated that immature defenses scores are directly associated with several indices of poorer mental health and poorer adaptiveness, including depression [28], anxiety disorders [28,57], personality disorders [58], alexithymia [36], poorer coping styles [37], and poorer marital adjustment [37]. Lesser mature defenses scores and more neurotic defenses scores tend to be associated with poorer functioning, but these relationships are less consistent than those obtained for immature defenses [28,36,40].…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…There are still, however, a few researchers who maintain that ''clitoral'' orgasm is somehow ''inferior'' to ''vaginal'' orgasm (Brody, 2007). Brody and Costa (2008) and Costa and Brody (2007) have suggested that so-called ''vaginal'' orgasm (as opposed to clitoral orgasm) is associated with less use of ''immature'' psychological defence mechanisms and higher satisfaction with mental health and relationships.…”
Section: Definitions Of Orgasmmentioning
confidence: 97%
“…This view, that there is a mature and psychologically healthy form of female orgasm, has become less prevalent, but is still promoted more than 100 years after Freud's proposals. For example, there are those who argue that women experiencing orgasms in intercourse have better mental health than women who reach orgasms through other means (Brody and Costa, 2008). Similarly, there are self-help programs whose goal is for women to achieve orgasm solely from vaginal intercourse (Kline-Graber and Graber, 1975).…”
Section: Introductionmentioning
confidence: 99%